N '-(5-Chloro-2-hydroxybenzylidene)-3,4,5-trihydroxybenzohydrazide dihydrate - Alhadi, A.A.A.; Ng, S.W.; Ali, Hapipah Mohd (International Union of Crystallography, 2009)
The benzohydrazide molecule in the title dihydrate, C(14)H(11)ClN(2)O(5 center dot)2H(2)O, is non-planar, with the two aromatic rings at either side of the -C(=O)-NH-N=CH- unit forming a dihedral angle of 29.7 (2)degrees. The benzohydrazide molecule is linked to the water molecules by O-H center dot center dot center dot O and N-H center dot center dot center dot O hydrogen bonds, with other O-H center dot center dot center dot O hydrogen bonds leading to a layer structure.